Plant Part Selection and Preliminary Sufficiency Ranges for Sap Testing Interpretation of Greenhouse Herbs - Robert C. Hochmuth; Eric H. Simonne; Lei Lani Davis; Wanda L. Laughlin (EDIS, 2008)
HS-1123, a 4-page illustrated fact sheet by Robert C. Hochmuth, Eric H. Simonne, Lei Lani L. Davis, and Wanda L. Laughlin, describes the use of quick test in hydroponic greenhouse herb production. Includes figures to help identify the plant parts used for analysis in basil, cilantro, dill, mint, and oregano, references, and a table of typical nutrient ranges. Published by the UF Department of Horticultural Sciences, November 2007.